1996
DOI: 10.1016/0014-5793(96)00728-4
|View full text |Cite
|
Sign up to set email alerts
|

Levels of endogenous cytokinins, indole‐3‐acetic acid and abscisic acid during the cell cycle of synchronized tobacco BY‐2 cells

Abstract: Correlation between cell cycle progression and endogenous levels of plant hormones was studied in synchronized tobacco BY-2 cell suspension cultures. Sixteen different cytokinins, indole-3-acetic acid (IAA) and abscisic acid (ABA) were extracted using solid-phase anion exchange chromatography in combination with immunoaffinity purification, and quantified by mass spectrometry. No significant correlation could be identified for IAA and ABA. In contrast, there were sharp peaks in the levels of specific cytokinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
82
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 38 publications
(39 reference statements)
8
82
0
3
Order By: Relevance
“…JA has been reported to change the ratio between cytokinin ribosides and free bases and to decrease the level of zeatin in potato (Solanum tuberosum; Dermastia et al, 1994). In BY-2 cells, zeatin levels peak sharply before G2/M transition (Redig et al, 1996), and its exogenous supply can rescue G2 arrest caused by the inhibition of cytokinin production (Laureys et al, 1998). However, a block of G2/M transition caused by JA could not be recovered by zeatin treatment (data not shown).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…JA has been reported to change the ratio between cytokinin ribosides and free bases and to decrease the level of zeatin in potato (Solanum tuberosum; Dermastia et al, 1994). In BY-2 cells, zeatin levels peak sharply before G2/M transition (Redig et al, 1996), and its exogenous supply can rescue G2 arrest caused by the inhibition of cytokinin production (Laureys et al, 1998). However, a block of G2/M transition caused by JA could not be recovered by zeatin treatment (data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…However, the activity of phosphatase cdc25, which activates cyclindependent kinase (CDK) by the removal of a phosphate group from a Tyr moiety in the ATP-binding loop, has also been shown to be cytokinin dependent (Zhang et al, 1996). Redig et al (1996) demonstrated that the zeatin level fluctuates in synchronized tobacco BY-2 cells, peaking at late S and before G2/M transition. When zeatin production was blocked, mitotic activity ceased and could only be restored by application of exogenous zeatin (Laureys et al, 1998), suggesting that cytokinins are essential not only for the initiation of the cell cycle but also for the progression through it.…”
mentioning
confidence: 99%
“…This nuclear labeling observed with anti-zeatin antibody is intriguing in light of the observations made by Redig et al (1996b). By using a synchronized cytokinin autotrophic cell culture (BY2) (Nagata et al, 1992), they found that only zeatin was present during the whole-cell cycle, with a short, transient accumulation of this cytokinin type at the end of the S phase and during the M phase.…”
Section: Discussionmentioning
confidence: 87%
“…The reduced meristem activity seen in the triple mutant roots seems to be a consequence of a delay in the G 2 3M phase, as demonstrated by FACS experiments. Interestingly, a sharp increase in the levels of zeatin, zeatin riboside, and zeatin riboside-5Ј-monophosphate was reported in tobacco cell cultures at the G 2 3M phase transition (34).…”
Section: Discussionmentioning
confidence: 96%